The Effect of 8 Weeks of Strength Training on the Ground Reaction Force in Single-leg Landing in Semi-professional Male Basketball Players - Sahar Farokhi; Mohammad Yousefi; Mohialdin Bahari (Shahid Beheshti University of Medical Sciences, 2023)
Background and Aims Single-leg landing is a difficult task for the lower limbs. This movement is very common in basketball and is one of the main causes of lower limb injuries, especially anterior cruciate ligament injuries. Single-leg landing causes a ground reaction force and torque to the lower limb. By increasing the internal torque and controlling the reaction force at the level of its application, the muscular strength of the lower limb can control the ground reaction force of the surface applied to the limb. This study aims to investigate the effects of 8 weeks of strength training on the ground reaction force in single-leg landingMethods In this study, 20 semi-professional male basketball players were divided into two equal groups of test and control. The samples of both control and test groups were asked to perform three single-leg landings from a 40-cm platform on the force plate. Then, the test group underwent 8 weeks of lower limb strength training, and after the end of the training, the members of the test and control groups were asked to repeat the landing movement. An average of three movements per person was considered. For data analysis, the paired t test was used for intra-group comparison, and the 1-way ANCOVA method was used to compare inter-group effects. Statistical analysis of the study was performed using SPSS software version 20, at a significance level of 0.05 for all tests.Results The results showed that the training program had no significant effects on the ground reaction force in the X direction in both internal and external directions, as well as, in the Y direction in the anterior and posterior directions, both within the group and between the groups. But, the training program had a significant and incremental effect on both within the group (P=0.005) and between the groups (P=0.002) in the Z direction.  Conclusion The strength training program lacks enough effect to reduce ground reaction force applied to semi-professional basketball players during a single-leg landing movement.